LabDisk with complete reagent prestorage for sample-to-answer nucleic acid based detection of respiratory pathogens verified with influenza A H3N2 virus. Issue 1 (26th November 2015) - Stumpf, F.; Schwemmer, F.; Hutzenlaub, T.; Baumann, D.; Strohmeier, O.; Dingemanns, G.; Simons, G.; Sager, C.; Plobner, L.; von Stetten, F.; Zengerle, R.; Mark, D.
Abstract : Sample supply remains the only manual handling step for pathogen detection at the point-of-care. Abstract : Portable point-of-care devices for pathogen detection require easy, minimal and user-friendly handling steps and need to have the same diagnostic performance compared to centralized laboratories. In this work we present a fully automated sample-to-answer detection of influenza A H3N2 virus in a centrifugal LabDisk with complete prestorage of reagents. Thus, the initial supply of the sample remains the only manual handling step. The self-contained LabDisk automates by centrifugal microfluidics all necessary process chains for PCR-based pathogen detection: pathogen lysis, magnetic bead based nucleic acid extraction, aliquoting of the eluate into 8 reaction cavities, and real-time reverse transcription polymerase chain reaction (RT-PCR). Prestored reagents comprise air dried specific primers and fluorescence probes, lyophilized RT-PCR mastermix and stick-packaged liquid reagents for nucleic acid extraction. Employing two different release frequencies for the stick-packaged liquid reagents enables on-demand release of highly wetting extraction buffers, such as sequential release of lysis and binding buffer. Microfluidic process-flow was successful in 54 out of 55 tested LabDisks. We demonstrate successful detection of the respiratory pathogen influenza A H3N2 virus in a total of 18 LabDisks with sample concentrations down to 2.39 × 10 4 viral RNA copies per ml, which is in the range of clinical relevance. Furthermore, we detected RNA bacteriophage MS2 acting as internal control in 3 LabDisks with a sample concentration down to 75 plaque forming units (pfu) per ml. All experiments were applied in a 2 kg portable, laptop controlled point-of-care device. The turnaround time of the complete analysis from sample-to-answer was less than 3.5 hours.